Le verre : science et technologie - Barton, James (Matériaux. Chimie., 2005)
This book is a compendium of Mat Hillert's publications. Mat Hillert is a world specialist in metal alloy at the origin of a universal computing code used to calculate the diagrams of phase. This work is in English.